1995
DOI: 10.1021/es9501225
|View full text |Cite
|
Sign up to set email alerts
|

Organic Cosolvent Effects on Sorption Equilibrium of Hydrophobic Organic Chemicals by Organoclays

Abstract: Isotherms were measured for sorption of naphthalene and diuron by four organoclays in equilibrium with various mixtures of methanol and water. The organoclays were prepared from Wyoming montmorillonite by replacing the natural exchangeable cations of the clay by the quaternary ammonium ions TMA (tetramethylammonium), TMPA (trimethylphenylammonium), HDTMA (hexadecyltrimethylammonium), and BDTDA (benzyldimethyltetradecylammonium). TMPA-clay showed the greatest sorptive capacity for naphthalene, while BDTDA-clay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 30 publications
3
53
0
1
Order By: Relevance
“…Ex situ remediation may gradually be replaced by in situ remediation (Sui et al 2003). Among the many in situ remediation technologies, remediation of contaminated soils and groundwaters by organoclays has been a topic under development (Wang et al 1997;Pernyeszi et al 2006;Nzengung et al 1996;Ö zcan et al 2006;Zhou et al 2006;Oyanedel-Craver et al 2006;Hermosín et al 2006). Organoclays are synthesized by exchanging the naturally occurring inorganic cations with organic cations.…”
mentioning
confidence: 99%
“…Ex situ remediation may gradually be replaced by in situ remediation (Sui et al 2003). Among the many in situ remediation technologies, remediation of contaminated soils and groundwaters by organoclays has been a topic under development (Wang et al 1997;Pernyeszi et al 2006;Nzengung et al 1996;Ö zcan et al 2006;Zhou et al 2006;Oyanedel-Craver et al 2006;Hermosín et al 2006). Organoclays are synthesized by exchanging the naturally occurring inorganic cations with organic cations.…”
mentioning
confidence: 99%
“…Four sorption experiments were conducted using 14 C-labeled PCE and TCE from Sigma (Nzengung et al, 1996 and. Sorption batch experiments were set up using techniques similar to those previously described.…”
Section: Sorption Experimentsmentioning
confidence: 99%
“…As a result, the partitioning coefficient increases when the co-solvent fraction in the solution decreases. Increasing the co-solvent percentages in the solution will be accompanied by higher water solubility of organic components which results in lower affinity to the sorbents (Nzengung et al 1996). Rao et al (1990) concluded a similar result.…”
Section: Effect Of Aqueous Environmentmentioning
confidence: 82%
“…Previous studies indicated that the co-solvent may inhibit the sorption of organic sorbates onto organoclays (Nzengung et al 1997). The study of Nzengung et al (1996) Also, the effect of temperature on the sorption tendency of sorbents has been studied. Chiou et al (1979) indicated that the sorption of 1, 1, 1 -trichloroethane increases at higher temperature.…”
Section: Figure 2-4 Effective Factors In the Sorption Process Of Sormentioning
confidence: 99%
See 1 more Smart Citation